Can Accounting Information Act As A - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2003)
This paper reviews and Sidnimarizes previous winks and the rationale for the proposition that accounting information is in fact value relevant in the determination of an initial public offering (IPO). Theoretical and empirical evidence has indicated that certain accounting measures can be used as proxies for total firm risk. that is, they could determine the riskiness ()fa corporation. The literature also advocates that accounting information is relevant in determining the value and thus the riskiness of a corporation through the use of accounting analysis. Since most of the information available in the prospectus is accounting information. it is arguable that this information represents a potential source for assessing the issuing firm. Some scholars have also advocated the possibility of using accounting information in assessing the value of fiat making an IPO. NIIMerOus papers have provided analytical and empirical evidence of the association between accounting numbers and the value of IPOs. The conclusion generally conies to show that information in the prospectus is value relevant concerning the IPO. The pâtper shows that it is indeed an arguable to use accounting information in the valuation of an IPO. Accordingly, it is an empirical issue whether accounting information has the property in explaining the ex ante uncertainly of an IPO.